Should I exercise or sleep to feel better? A daily analysis with physically active working mothers. (March 2015) - Fortier, Michelle S.; Guerin, Eva; Williams, Tamara; Strachan, Shaelyn
Abstract: Problem: Positive affect is a determinant of physical and mental health, as well as happiness. Working mothers may miss out on these benefits as they report relatively low positive affect. Physical activity and sleep are associated with the enhancement of positive affect and may offer working mothers an avenue for improving positive affect. This study's main purpose was to examine daily positive affect as a function of physical activity intensity and daily sleep satisfaction among working mothers. A secondary purpose was to examine the possible bi-directional relationship between physical activity intensity and daily sleep satisfaction, given previous evidence of associations between sleep and physical activity. Method: In this experience sampling study, 63 physically active working mothers reported the intensity of each physical activity session as well as their daily sleep satisfaction and end-of-day positive affect over 14-days using personal electronic devices. Results: Hierarchical Linear Modeling revealed that both previous night sleep satisfaction ( t (752) = 3.05, p  < .01) and same-day intensity of physical activity (, t (752) = 3.59, p  < .001) were positively related to daily positive affect. Only physical activity intensity showed a significant relationship with positive affect when both predictors were included in a model. There was no support for reciprocal relationships between sleep satisfaction and physical activity intensity. Discussion: These findings suggest that the robust association between daily physical activity and positive affect extends to working mothers and that choosing physical activity as a self-care activity is a good investment for this population.